Factors That Influence Rural Entrepreneurship: Case-Study Evidence from Torbat-E Heydarie, Kadkan District - Abbasi, Mostafa (2021)
Entrepreneurship is an important instrument in planning and realizing rural community development. Owing to current problems in societies, focusing on the rural entrepreneurship is of utmost importance. Entrepreneurship by creating new opportunities for employment and income plays an important role in improving socioeconomic conditions of villages. The aim of this study is to assess the factors influencing the development of rural entrepreneurship in a case study of villages in Torbat-e Heydarieh, Kadkan district. The research method was descriptive-analytic, and the data collection method was library and field studies. For data analysis, One-sample t-test with principal component analysis was used. The statistical population of the study was the villagers of Kadkan district of Torbat-e Heydarieh, from which 240 people were asked to complete a questionnaire. The validity of the questionnaire was evaluated using the Content and face validity with expert judgement. Reliability of the questionnaire was examined by Cronbach's alpha coefficient which for all studied domains was above 0.75 which indicated that questionnaire was satisfactory. The results indicated that economic factor was the most influential issue in the rural entrepreneurship. The results also showed that rural entrepreneurship provides a good context for creating jobs in agricultural and non-agricultural sectors and it is an important factor for achieving sustainable rural development.